Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Motivasi Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan - Bodroastuti, Tri; Riszaeni, Riszaeni; Suhaji, Suhaji (STIE Widya Manggala, 2018)
This study aims to analyze the effect of Organizational Culture, Organizational Commitment, and Work Motivation to Employee Statisfaction andPerformance (case study on PT. Pandowo Utomo Food Semarang). The population in this study is all employees of PT. Pandowo Utomo Food distribution section totaling 157 people. The number of samples proposed in this study is the entire population that amounted to 157 people. In this study did not use sampling technique, because the number of samples used in this study were all population (census). The analytical tool used in this study is SEM based component or variance-PLS. The result of the study stated that Organizational Culture and Work Motivation have a significant positive effect on Job Statisfaction, while Organizational Commitment has no significant positive effect on Job Statisfaction. Organizational Culture has a significant positive effect on EmployeePerformance, while Organizational Commitment, Work Motivation, and Job Statisfaction have no significant effect on Employee Performance.